TRANSLATION TECHNIQUES AND QUALITY OF THE TRANSLATION OF LEGAL TEXT ON IMMIGRATION LAW - Della Fransiska Ginting; Syahron Lubis; Umar Mono (International Journal of Humanity Studies (IJHS), 2020)
This research aims to (1) analyze translation techniques by using Molinas Albirs theory (2002) in the text of the Immigration Law in English, (2) analyze the quality of the translation in terms of accuracy, acceptability and readability by using Nababan's theory (2012) in translating legal of the Immigration Law into English; and (3) analyze the impact of translation techniques on the quality of the translation in the text of the Immigration Law in English. This research is qualitative research with a descriptive approach. The source of data is the Immigration Law written in two languages, namely Indonesian as the source text (TS) and English as the target language (TL). Based on the analysis, it is found that: (1) In the translation of the Immigration Law, there are 12 translation techniques used, namely 64 (39%) literal, 36 (22%) calque, 24 (14%) established equivalent, 10 (6.2%) generalization, 9 (5.5%) borrowing, 4 (2,4%) linguistic amplification, 2 (1.2%) particularization, 5 (3.1%) transposition, 1 (0.6%) compensation, 3 (1.8%) modulation, 2 (1.2%) reduction and 1 (0.6%) adaptation. (2) The total score for the translation quality is 2,77% which is the quality of translation almost perfect. (3) The most dominant translation technique used in translating this legal text is literal technique (39%) which is the dominant technique that gives impact to translation quality.